Music piracy and neutralization: A trajectory analysis from short-term longitudinal - Marcum, Cathy (2008)
Digital piracy is an emerging criminal behavior. Little empirical research has been produced that examines the role of neutralization and performance of this behavior. Using short-term longitudinal data from college students, the present study examines the trajectories of digital piracy and the role of neutralization. The findings from this study show that trajectories of digital piracy may be tied to neutralization toward digital piracy. Criminal justice policies may be developed from this study